Influence of heat-treatment protocols on mechanical behavior of lithium silicate dental ceramics - Alves, Manuel Fellipe Rodrigues Pais; Simba, Bruno Galvão [UNESP]; de Campos, Leonardo Queiroz Bueno; Ferreira, Iago; dos Santos, Claudinei (My University, 2019)
In this work, three different commercial lithium silicate (LS) glass-ceramics for computer aided design/computer aided machining systems, CeltraDuo-Dentsply (LS-C), E-MaxCAD-Ivoclar (LS-E), and Suprinity-Vita (LS-S), were comparatively characterized. Following the protocols recommended by the manufacturers, the glass-ceramics were heat-treated under low vacuum and characterized by X-ray diffraction, scanning electron microscopy, hardness, fracture toughness, Young's modulus, and flexural strength. Rietveld refinement indicated that the materials “as-received” present mostly amorphous phase and Li2SiO3 as secondary crystalline phase in LS-E and LS-S specimens, while LS-C specimens also present Li2Si2O5 and Li3PO4 as crystalline phases. All “as-received” glass-ceramics present hardness, fracture toughness, and Young's modulus of around 647-678 HV, 1.15-1.40 MPa.m1/2, and 82-92 GPa, respectively. After heat treatment, the LS-C and LS-S specimens presented decreasing of amorphous phase associated to Li2SiO3 and Li2Si2O5 grains with low aspect ratio, while LS-E indicates a reduction of amorphous phase and Li2Si2O5 elongated grains. Fracture toughness and Young's modulus increase about 10% due to the crystallization of residual amorphous phase for all materials. Moreover, crystallographic and microstructural characteristics are responsible for the higher flexural strength of LS-E (327 MPa), regarding LS-C and LS-S. However, the glass-ceramics LS-E present lower Weibull modulus (m = 5.4) comparatively to LS-C (m = 9) and LS-S (m = 6).
Keywords: crystallization; dental glass-ceramics; heat treatment; mechanical properties; microstructure